2015
DOI: 10.1016/j.seizure.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Experience from therapeutic drug monitoring and gender aspects of gabapentin and pregabalin in clinical practice

Abstract: Gabapentin and pregabalin are more used in women than in men, and routine use of TDM is most common in patients with epilepsy. Pharmacokinetic variability is extensive, highlighting a need for individualisation of therapy regardless of indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 11 publications
4
14
0
Order By: Relevance
“…These results are consistent with the reported studies related to pharmacokinetic variability of pregabalin which emphasize that pregabalin has extensive pharmacokinetic variability and that age and gender are contributing factors of this variability which elucidates the need for individualization of therapy and TDM [27,28]. ▶table 1 Steady state trough and maximum plasma and saliva pregabalin levels (ng/ml) in 44 patients enrolled in this study.…”
Section: Resultssupporting
confidence: 90%
“…These results are consistent with the reported studies related to pharmacokinetic variability of pregabalin which emphasize that pregabalin has extensive pharmacokinetic variability and that age and gender are contributing factors of this variability which elucidates the need for individualization of therapy and TDM [27,28]. ▶table 1 Steady state trough and maximum plasma and saliva pregabalin levels (ng/ml) in 44 patients enrolled in this study.…”
Section: Resultssupporting
confidence: 90%
“…We found extensive pharmacokinetic variability among the included patients as demonstrated by the 22-fold range in C/D ratios, in line with the known variability in bioavailability, 11 the effect of renal function on clearance 28 and previous findings from clinical practice. 29 The observation that the C/D ratio was higher in elderly patients (≥65 years) also confirms previous findings. 29,30 It has been suggested that changes in renal function are responsible for age-related changes in GBP pharmacokinetics, 28 but as we did not have information on renal function at the time of serum concentration measurement, we could not examine this.…”
Section: Pharmacokinetic Variability From Retrospective Tdm Datasupporting
confidence: 88%
“…29 The observation that the C/D ratio was higher in elderly patients (≥65 years) also confirms previous findings. 29,30 It has been suggested that changes in renal function are responsible for age-related changes in GBP pharmacokinetics, 28 but as we did not have information on renal function at the time of serum concentration measurement, we could not examine this.…”
Section: Pharmacokinetic Variability From Retrospective Tdm Datasupporting
confidence: 88%
“…HVA calcium channels may also be targeted for the treatment of seizures. Gabapentin is used as an anticonvulsant to treat focal and partial seizures 148 . However, given that this compound has the propensity to affect multiple types of HVA channels through its interaction with Cavα2δ subunits, it is not clear how this compound mediates its clinical effects at the cellular level.…”
Section: Lamotriginementioning
confidence: 99%